MEDICAL STUDENTS’ SUICIDES –A SYSTEMATIC REVIEW - ANNIKA MARTIN, ERIKA JÄÄSKELÄINEN, JOUKO MIETTUNEN, SAARA KAAKINEN, TUULA HURTIG, ANU-HELMI HALT (Psychiatria Fennica)
ABSTRACT Objectives: Suicidal tendencies among physicians have been a subject of research and scientific interest for some time, but less is known about suicides and the factors associated with them in the case of medical students, i.e. future physicians, although some interest has been shown in symptoms of depression and suicidal ideation. The authors’ aim was therefore to present an up-to-date systematic review of medical students’ suicides and associated factors. Materials and methods: The authors searched for original articles published in English that reported at least one medical student’s suicide by consulting several databases in October 2020 and conducting additional searches in recent publications in August 2022 and February 2023. Data on the characteristics of the research, and the numbers of suicides and associated factors were collected from the articles identified. The guidelines of the Meta-analysis Of Observational Studies in Epidemiology (MOOSE) were applied throughout. Results: After the removal of duplicates, the initial search yielded 1,401 articles for further screening, whereupon full-text assessment of 56 of these revealed 17 that met the inclusion criteria. Screening of the references in the accepted articles, together with the additional searches, identified a further 11 eligible articles, making a total of 28, based on 18 populations. The methods used in these articles and the suicide rates reported varied, but based on nine studies, the median of annual suicide rates per 100,000 was 10.1. Being in the last years of studying, having previous mental health problems or problems in personal relationships and academic stress were the most frequently reported associated factors. Conclusions: More systematic research and official medical student death records are needed in order to achieve a better understanding of this subject and improve the wellbeing of medical students.